THE VEGETATIVE ANATOMY OF KOSTERMANSIA MALAYANA SOEGENG - Baas, P. (Research Center for Biology, 1972)
The anatomy of leaves, twigs, wood and seedling of Kostermansia Soegeng is described. A comparison with some species of Coelostegia and Durio indicates the close affinities between the three taxa, but also shows some differences in leaf anatomy, probably valuable for diagnostic purposes. The stomata in Kostermansia show a very remarkable arrangement in circles around the insertions of the scales.